Penegakan Hukum Pidana terhadap Penambangan Emas Tanpa Izin (PETI) di Kabupaten Bungo: Analisis Perspektif Hukum Islam - Kiki Heriyanto; Abdul Halim (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
In Indonesia, illegal gold mining (PETI) is still a persistent environmental crime, especially in resource-rich areas like Bungo Regency, Jambi Province. The efficacy of local law enforcement is still in doubt, despite the fact that Article 158 of the modified Mining Law (Law No. 3 of 2020) offers a solid legal foundation for criminal penalties. The purpose of this study is to evaluate the efficacy of criminal law enforcement in Bungo Regency against PETI from the standpoint of Islamic law based on maqāṣid al-sharī‘ah. This study uses a juridical-empirical approach, combining pertinent court rulings, field data from law enforcement, and normative legal analysis. The results show that although legal measures like arrests and convictions have been carried out, they have not had a major deterrent effect. The overall effect of enforcement operations is weakened by structural issues, such as the economic dependence of local populations, the scarcity of alternative livelihoods, and the difficulties of prosecuting informal financiers. According to maqāṣid al-sharī‘ah, illicit mining is incompatible with the defense of basic principles, especially the preservation of life (ḥifḍ al-nafs), property (ḥifṢ al-māl), and environmental sustainability. The study comes to the conclusion that effective law enforcement necessitates an integrated strategy that combines preventive and rehabilitative tactics, such as economic empowerment, legal awareness campaigns, and regular supervision, with repressive measures. A more equitable, long-lasting, and socially conscious form of environmental criminal law enforcement is provided by combining positive law with the ethical framework of maqāṣid al-sharī‘ah.